2017
DOI: 10.14569/ijacsa.2017.081004
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors Plays a Vital Role in ERP Implementation in Developing Countries: An Exploratory Study in Pakistan

Abstract: Abstract-The capabilities of an Enterprise ResourcePlanning (ERP) system to integrate all the business functions needed in a single system with a shared database efficiently and effectively has persuaded organizations to adopt them. In enterprise environment, successful ERP implementation has played a vital role for organizational efficiency. In this respect critical success factors (CSFs) have been identified essential for the successful ERP implementation. The purpose of this paper is to identify and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
53

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(76 citation statements)
references
References 23 publications
0
22
0
53
Order By: Relevance
“…The first form of categorization concerns the classification of factors into organizational, project, human, technological/ERP and external partners (vendors-consultants) categories [9,25,28] (Table VI). 31 | P a g e www.ijacsa.thesai.org…”
Section: A First Form Of Categorization: Erp Orientations Of Implemementioning
confidence: 99%
See 1 more Smart Citation
“…The first form of categorization concerns the classification of factors into organizational, project, human, technological/ERP and external partners (vendors-consultants) categories [9,25,28] (Table VI). 31 | P a g e www.ijacsa.thesai.org…”
Section: A First Form Of Categorization: Erp Orientations Of Implemementioning
confidence: 99%
“…In particular, [6] argue that ERP uses a central database that collects and organizes data in real time in order to achieve this integration between business operating domains. Additionally, ERP system leads to the acquisition of many business advantages, such as operational efficiency and effectiveness, easy access to reliable information, maintenance of the competitive advantage, reduce the complexity of processes, profit increase and reduce cost [4,5,[7][8][9][10][11][12]. In addition to its wide range of practical applications, ERP system is an equally active area of research interest [13].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, ERP is not perfectly matched with the users" need of the system because it provides standardised processes or features to support work procedures or user tasks. Changes in users" requirements that cover all business processes are also likely to happen after the initial implementation phase due to both internal (improvement of business process and redesign projects) and external (competitors or changing government regulations) (Ahmed, Shaikh & Sarim, 2017;Ha & Tran 2018). ERP is embedded into an evolving task environment.…”
Section: Enterprise Resource Planning (Erp)mentioning
confidence: 99%
“…ERP installation also requires a lot of resources and finance to get the desired results. Many researchers suggested determinants of ERP implementation in multiple industrial sectors and critical factors have been identified in diverse contexts (Ahmed, Shaikh, & Sarim, 2017;Ali, Hussin, Othman, Elzamly, & Doheir, 2018;Baskaran, 2018). Some found the sociological factors and technological aspects (Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%